Propagação vegetativa de jambeiro vermelho [Syzygium malaccense (L.) Merr. & L.M. Perry] - de Almeida, Eduardo José [UNESP]; Scaloppi, Eliana Mayra Torrecillas [UNESP]; de Jesus, Natanael; Benassi, Antonio Carlos; Ganga, Rita Maria Devós; Martins, Antonio Baldo Geraldo [UNESP] (FapUNIFESP (SciELO), 2010)
The Malay Apple [Syzygium malaccense (L.) Merr. & L.M. Perry] is an option for the producer as its fruits are attractive and well accepted by the consumer. The difficulty of culture of this species is that the plant is very tall and has a long juvenile period when propagated by seed, making its vegetative propagation necessary to anticipate the productive period and decrease its size. The possibility of vegetative propagation of this species was studied by cutting, layering, and grafting. In the cutting experiment, three doses of indolbutyric acid (IBA) (0, 1,000, 3,000, and 5,000 mg L-1) were tested in two lengths of herbaceous cuttings (15 and 25 cm). In the layering experiment, two periods of layering (summer and autumn) and four doses of IBA (0, 1,000, 4,000, 7,000, and 10,000 mg kg-1) were evaluated. For grafting, the compatibility between S. malaccense and S. jambos (L.) Alston as rootstock was studied with two diameters (0.5 and 0.8 cm) and in two periods (winter and summer), by method of full graft. For cuttings, the percentage of rooting was 20%, independently of the IBA doses, except for 5,000 mg L-1 that showed negative effect on 15 cm cuttings; layering and grafting were not successful in the studied conditions.
Vegetative propagation of Malay apple [Syzygium malaccense (L.) Merr. & L.M. Perry]
Keywords: Auxins; Cutting; Grafting; Layering